2010
DOI: 10.1007/s10327-010-0229-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic and biological characters of Japanese potato strains of Ralstonia solanacearum

Abstract: We assessed the geographic distribution, biovar, phylotype, DNA fingerprints (rep-PCR), and/or endoglucanase sequence of potato bacterial wilt pathogen, Ralstonia solanacearum (Rs), in Japan. Rs has been isolated from potato fields in southwestern, warm, temperate regions. Of the 188 isolates, 74 belonged to biovar N2 (39%), 44 to biovar 3 (24%), and 70 to biovar 4 (37%). Biovars N2 and 4 strains were widely distributed, from northern (Hokkaido) to southern (Okinawa) Japan. Based on the results of multiplex-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
0
18
0
3
Order By: Relevance
“…Both biovar 4 (phylotype I) and biovar N2 (phylotype IV) strains are common and widely isolated from Hokkaido to Okinawa. On the other hand, biovar 3 (phylotype I) strains are found in limited areas (Nagasaki and Okinawa Prefectures) in Japan (Horita et al 2010). From a plant quarantine point of view, phylotype II/biovar 2 (American strains) strains have not yet been reported in Japan (Elphinstone 2005;Nouri et al 2009;Swanson et al 2005), since only domestic seed potatoes have been distributed for cultivation and the import of the seed potatoes from foreign countries has been strictly prohibited by a plant protection law .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Both biovar 4 (phylotype I) and biovar N2 (phylotype IV) strains are common and widely isolated from Hokkaido to Okinawa. On the other hand, biovar 3 (phylotype I) strains are found in limited areas (Nagasaki and Okinawa Prefectures) in Japan (Horita et al 2010). From a plant quarantine point of view, phylotype II/biovar 2 (American strains) strains have not yet been reported in Japan (Elphinstone 2005;Nouri et al 2009;Swanson et al 2005), since only domestic seed potatoes have been distributed for cultivation and the import of the seed potatoes from foreign countries has been strictly prohibited by a plant protection law .…”
Section: Introductionmentioning
confidence: 97%
“…Distribution of races 1, 3, and 4 and biovars N2, 3, and 4 have been clarified (Horita and Tsuchiya 2001;Horita et al 2005Horita et al , 2010Morita et al 1996;Tsuchiya 2008;Yano et al 2005).…”
Section: Introductionmentioning
confidence: 97%
“…A third study with Asian strains by Villa et al (2005) showed high diversity of Asian strains and the grouping of strains from America, Africa and Europe in a separate cluster. A more recent study with Japanese strains (Horita et al 2010) showed that phylotype I and IV strains are common in potato areas. The absence of phylotype II that predominates in the Americas is most likely due to the fact that strains move between areas in seed potatoes, and in Japan only domestic seed potatoes have been used since 1951.…”
Section: Introductionmentioning
confidence: 98%
“…Accurate identification of the causal pathogen is necessary because management strategy is almost different for different organisms. The usual method of identification of the causal bacterial plant pathogen involves isolation, pathogenicity test followed by Gram staining, microscopic studies, growing them on selective medium, a series of biochemical tests and carbohydrate tests and studies at molecular levels followed in different countries like Japan and Mauritius (Rodney et al, 2010;Harita et al, 2010;Suga et al, 2013). Molecular level of isolation and characterization of the phytopathogenic bacteria has recently gained wide acceptance (Tamura et al, 2011;Zhou et al, 2012 (Kumar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%